Eco-Friendly Fashion and Personal Values: Revealing the Hidden Forces behind Attitudes and Purchase Intentions - Rossanty, Yossie; Nasution, Muhammad Dharma Tuah Putra (International Review of Management and Marketing, 2025)
The aim of this study is to investigate how personal value orientations—altruistic, biospheric, and egoistic—influence consumers' attitudes towards eco-friendly fashion brands and their purchase intentions. Data were gathered through a survey of 389 potential consumers in Indonesia, selected via simple random sampling and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that personal value orientations significantly impact both attitudes and purchase intentions towards eco-friendly fashion brands. Although the values were not assessed individually, they collectively represent consumers' overall value orientations. Additionally, pro-environmental attitudes emerged as a crucial determinant of purchase intentions. The demographic analysis provided further insights into attitudes and behaviors related to eco-friendly practices. The study highlights practical implications for marketers, emphasizing the importance of aligning promotional strategies with consumers' personal values to enhance engagement and purchase intentions. Furthermore, a comprehensive understanding of demographic variables is essential for crafting targeted marketing campaigns. This research contributes to the Value-Belief-Norm (VBN) theory by providing empirical evidence on how personal value orientations shape consumer attitudes and purchase intentions towards eco-friendly fashion. The study acknowledges limitations and suggests that future research should include diverse cultural and geographic samples and explore other eco-friendly product categories.